Experimental and Computational Approaches of Newly Polymorphic Supramolecular H-Bonded Liquid Crystal Complexes - Al-Mutabagani, Laila A.; Alshabanah, Latifah Abdullah; Naoum, Magdi M.; Hagar, Mohamed; Ahmed, Hoda A. (Frontiers in Chemistry, 2020)
New 1:2 liquid crystalline supramolecular H-bonded complexes (SMHBCs) were synthesized through double H-bond interactions between 4-(nicotinoyloxy) phenyl nicotinate as the base component and two molecules of 4-n-alkoxybenzoic acid (An). The base component was expected to be in two conformers according to the orientation of the N atom and the carboxylate group, syn conformer (I) and anti-conformer (II). DFT calculations revealed that only one of the two possible conformers of I exists, and the addition of the two molecules of the alkoxy acids (An) did not affect its conformation. Mesomorphic properties of all of the prepared complexes (I/An), bearing different terminal flexible alkoxy chains were investigated, and the formation of H-bonds confirmed by differential scanning calorimetry (DSC), and the phases identified by polarized optical microscopy (POM), and FT-IR spectroscopy. Highly thermally stable mesophases possessing broad temperature ranges were observed for all investigated complexes compared to their individual components. Depending on the length of the terminal flexible alkoxy chain, the prepared SMHBCs showed to exhibit di- or tri-morphic enantiotropic mesophases. The effect of replacing one of the –COO– connecting unit by an azo group (-N=N-) in the basic molecule (I), on the mesomorphic properties has been investigated experimentally (via DSC) and theoretically (via DFT). The DFT calculations revealed that the polarizability, the dipole moment, and the aspect ratio of the investigated SMHBCs are lower than those of their corresponding ester/azo analogues. All these factors rationalize the enhanced smectic mesophase ranges of the complexes compared with those of the ester/azo analogues. The high aspect ratios and dipole moments of the SMHBCs of the azo derivative enforces the lateral intermolecular attraction that permit the formation of the more ordered smectic C mesophase with respect to the enhanced polymorphic mesophases of the diester derivative.